1994
DOI: 10.1007/bf02444314
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of generalized wound infection in immunized rats

Abstract: The occurrence of the pyocyanic bacillus in the blood and spleen is compared after intramuscular administration to intact and immunized animals. It is demonstrated that blood clearance is performed by transferring the causative agent to splenic phagocytes. It is suggested that antibodies agglutinize the microorganisms in the primary focus of infection and prevent their entry into the blood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1996
1996
1999
1999

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The majority of bacterial cells in the control remained unchanged. The early signs of bacteriopyknosis, i.e., conversion of bacteria into detritus [3,4], were seen. There were intermediate forms between bacteria and detritus, i.e., bacterial cells with pronounced deformations (Fig.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The majority of bacterial cells in the control remained unchanged. The early signs of bacteriopyknosis, i.e., conversion of bacteria into detritus [3,4], were seen. There were intermediate forms between bacteria and detritus, i.e., bacterial cells with pronounced deformations (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Some animals were sacrificed 0007-4888/96/0009-0956515.00 9 1997 Plenum Publishing Corporation under ketamine narcosis 0.5 to 22 h after the injection, and the sites of infection were studied morphologically. The antibody titer was determined by the agglutination reaction [3]. The significance of differences was evaluated by the Wilcoxon t e s t .…”
Section: Methodsmentioning
confidence: 99%
“…The intensity of bacteriopyknosis was estimated by the mass of purulent-necrotic exudate formed in the site of injection 7 days after injection of microbial suspension. Previously, it was demonstrated that bacteriopyknosis inhibits phagocytosis and reduces the size of abscess [1,2]. The significance of differences was evaluated by Wilcoxon's test.…”
Section: Methodsmentioning
confidence: 99%
“…A relationship between erythrocyte damage and progressive microcirculatory disorders upon artificial [1,5,7] and assisted circulation [6] has been established. However, the information regarding the effect of direct cardiac massage (DCM) on peripheral blood erythrocytes is scanty.…”
Section: Abstract: Direct Cardiac Massage; Erythrocyte Morphology; Smentioning
confidence: 99%
See 1 more Smart Citation